Efektivitas Konsorsium Mikroalga Chlorella sp. dan Mikroba Indigenous Dalam Menurunkan BOD, COD, dan TN Air Limbah Industri Kecap Menggunakan MBBR - Zuhria Oktaviani; Novirina Hendrasarie (Jurnal Serambi Engineering, 2024)
The treatment of soy sauce effluent poses a significant environmental challenge due to its high levels of contaminants. Several studies have shown that the use of Chlorella sp. microalgae can contribute to the degradation of BOD, COD and TN using a moving bed biofilm reactor (MBBR). Therefore, this study aims to determine the effectiveness of a consortium of Chlorella sp. microalgae and indigenous microbes in treating soy sauce wastewater using an MBBR with an anoxic-oxic process. This research uses a continuous system with variations in the volume of alkaline media (20%, 40%, 60%) and sampling times (14, 26, 38 hours). The best variation for the reduction of organic content in soy sauce wastewater using the Chlorella sp. microalgae consortium achieved a BOD reduction of 71.54%, COD reduction of 74% and TN reduction of 71.89%, all at a sampling time of 38 hours. Meanwhile, the organic reduction using indigenous microbes showed a BOD reduction of 86.76%, COD reduction of 88.24% and TN reduction of 82.76%, all at a sampling time of 38 hours.